Endophilin A2 deficiency protects rodents from autoimmune arthritis by modulating T cell activation - Ulrika Norin (Nature Portfolio, 2021)
The autoimmune disorder, rheumatoid arthritis (RA), has been associated with multiple pathophysiological factors. Here the authors show that deficiency in endophilin A2 in rodents protects them from experimental arthritis by altering T cell activation threshold and effector functions, thereby hinting a potential target for RA therapy.